Effects of graphene oxide on the development of offspring mice in lactation period. (February 2015) - Fu, Changhui; Liu, Tianlong; Li, Linlin; Liu, Huiyu; Liang, Qinghua; Meng, Xianwei
Abstract: The potential toxicity of graphene oxide (GO) has attracted much attention with numerous promising biomedical applications in recent years. However, information about GO on the development of filial animals is rare. In this work, we studied the potential developmental toxicity of GO when they entered the body of maternal mice and their offspring by oral exposure with two doses. The results showed that the increase of body weight, body length and tail length of the filial mice received GO at 0.5 mg mL −1 (about 0.8 mg each mouse) every day in the lactation period was significantly retarded comparing with the control group. The anatomy and histology results revealed the delayed developments of offspring in high dosage group. We also evaluated the possible toxicological mechanism caused by GO and found that the length of the intestinal villus of the filial mice received high concentration GO were decreased significantly compared with the control group. It can be concluded that GO showed many negative effects on the development of mice in the lactation period. These findings can be significant for the development of graphene materials-based drug delivery system and other biomedical applications in the future.